2020
DOI: 10.3390/microorganisms8010111
|View full text |Cite
|
Sign up to set email alerts
|

Bioregional Alterations in Gut Microbiome Contribute to the Plasma Metabolomic Changes in Pigs Fed with Inulin

Abstract: Inulin (INU) is a non-digestible carbohydrate, known for its beneficial properties in metabolic disorders. However, whether and how gut microbiota in its regulation contributes to host metabolism has yet to be investigated. We conduct this study to examine the possible associations between the gut microbiota and circulating gut microbiota–host co-metabolites induced by inulin interventions. Plasma and intestinal site samples were collected from the pigs that have consumed inulin diet for 60 days. High-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 71 publications
1
25
1
Order By: Relevance
“…A previous work showed that l-leucine and l-valine are involved in regulation of food intake through gut satiety hormones [52], while other investigations have evidenced that these essential amino acids are associated with body weight regulation, insulin, and glucose homeostasis [53,54]. In a very recent study, Wu and colleagues identified l-leucine, l-isoleucine and l-valine as biomarkers in plasma of pigs that received an inulin supplement [55]. These branched amino acids were lower after inulin intervention and positively associated to total cholesterol and glucose levels [55]; nonetheless, these results are disagreed with the present study, because we detected a high content of l-leucine and l-valine which inversely correlated with cholesterol and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…A previous work showed that l-leucine and l-valine are involved in regulation of food intake through gut satiety hormones [52], while other investigations have evidenced that these essential amino acids are associated with body weight regulation, insulin, and glucose homeostasis [53,54]. In a very recent study, Wu and colleagues identified l-leucine, l-isoleucine and l-valine as biomarkers in plasma of pigs that received an inulin supplement [55]. These branched amino acids were lower after inulin intervention and positively associated to total cholesterol and glucose levels [55]; nonetheless, these results are disagreed with the present study, because we detected a high content of l-leucine and l-valine which inversely correlated with cholesterol and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Total bacterial DNA was extracted from the mucosa of pigs, using the Qiagen DNA isolation kit (Qiagen, Hilden, Germany), according to the manufacturer's instructions. For 16S ribosomal RNA (rRNA) gene-based microbial composition profiling, barcoded amplicons from the V3-V5 region of 16S rRNA genes were generated by a 2-step PCR protocol, and the 16S rRNA gene was sequenced on the Illumina HiSeq sequencing platform, as described before [25]. Raw Illumina fastq files were demultiplexed, quality filtered and analyzed, using QIIME 1.8.0 [26], as described previously [25], while using the Silva 123 reference database.…”
Section: Dna Extraction Pcr Amplification and Illumina Hiseq Sequencingmentioning
confidence: 99%
“…For 16S ribosomal RNA (rRNA) gene-based microbial composition profiling, barcoded amplicons from the V3-V5 region of 16S rRNA genes were generated by a 2-step PCR protocol, and the 16S rRNA gene was sequenced on the Illumina HiSeq sequencing platform, as described before [25]. Raw Illumina fastq files were demultiplexed, quality filtered and analyzed, using QIIME 1.8.0 [26], as described previously [25], while using the Silva 123 reference database. Predictive functional profiling of microbial communities was conducted by Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PIRCUSt) [27].…”
Section: Dna Extraction Pcr Amplification and Illumina Hiseq Sequencingmentioning
confidence: 99%
“…The nutrient composition of intestinal digesta is dependent of diet composition and processes of nutrient hydrolysis, fermentation, and absorption in the gut (14,15). Related complex changes in composition can be studied by measuring changes and differences in the gut metabolome (16,17). Metabolomics offer the possibility to study many metabolites simultaneously in a single sample (18).…”
Section: Introductionmentioning
confidence: 99%